Evaluation of an automated point‐of‐care test system for measuring thrombin–antithrombin complex in dogs. Issue 1 (17th December 2019) - Kato, Daiki; Takahashi, Masashi; Yonezawa, Tomohiro; Ohmi, Aki; Takeda, Sawako; Nakagawa, Taisuke; Hosoda, Saburou; Kanemoto, Hideyuki; Fukushima, Kenjiro; Ohno, Koichi; Matsuki, Naoaki; Tsujimoto, Hajime
Abstract: Objective: To evaluate the utility of the chemiluminescent enzyme immunoassay (CLEIA) method for point‐of‐care (POC) measurement of canine plasma thrombin–antithrombin complex (TAT) concentration. Assessment and Main Results: Plasma TAT concentration was measured in 54 healthy dogs and in 72 dogs with various diseases. A significant correlation was found between TAT concentration measured by CLEIA and that measured by an ELISA that was previously used in dogs. The upper limit of the reference value of TAT concentrations measured by CLEIA was determined to be 0.2 ng/mL based on the TAT concentration in 54 healthy dogs. TAT concentrations exceeded the reference interval in a portion of dogs when a hypercoagulable state may be present. Conclusions: Canine plasma TAT concentrations measured using CLEIA were correlated with that measured using ELISA. Hence, a POC testing instrument may be used for early detection of activation of thrombin generation in emergency and critical care settings.